Exercise, Asthma and the Olympics: A 2000-year-old tale - Del Giacco, Stefano (Porto Biomed J, 2016)
Two separated phenotypes of Exercise-Induced-Asthma exist. Olympic Athletes have won more medals than their non-asthmatic peers. Competitive swimmers show an increased asthma prevalence. Asthmatics have no limitations in sports practice if they receive adequate medical treatment. Aerobic exercise programs are beneficial for asthmatics and should be included in asthma action plans.